Lipidomic profiling of subchronic As4S4 exposure identifies inflammatory mediators as sensitive biomarkers in rats. Issue 3 (16th January 2019) - Zhou, Jing; Ma, Hongyue; Wu, Yuanyuan; Lv, Xiang; Wang, Jiajia; Liu, Shengjin; Li, Dandan; Wang, Hengbin; Yan, Yanqing; Luo, Niancui; Li, Quan; Xu, Huiqin; et al.
Abstract : Arsenic sulfide compounds provide nearly all of the world's supply of arsenic. Abstract : Arsenic sulfide compounds provide nearly all of the world's supply of arsenic. However, the risk of arsenic trisulfide exposure is still not fully investigated. Here, we systemically assessed the toxicology of As4 S4 in rats by combining arsenic metabolite detection, routine testing and lipidomic profiling. It was revealed that the oral administration of As4 S4 for two months increased the total arsenic content in the liver reaching a saturation level. Further analysis by anion exchange chromatography coupled with inductively coupled plasma mass spectrometry (ICP-MS) technology showed no trace of inorganic arsenic, but there was significant presence of dimethylarsinic acid (DMA), in the livers of rats. This arsenic metabolite was less toxic to rats and did not induce overt liver pathology and functional injury. In contrast, lipidomic profiling provided a comprehensive map of lipids and uncovered a more complex inflammatory response, exhibiting more sensitive change to arsenic exposure. We observed that metabolites of cyclooxygenase, including PGF2α, dhk PGF2α, 15k PGF2α, 8-iso-PGF2a, PGE2, dhk PGE2, PGD2, 15d-PGD2, and PGJ2, were significantly elevated. But mediators from lipoxygenase, cytochrome P450, docosahexaenoic acid, and eicosapentaenoic acid pathways were not markedly affected. In summary, we identified DMA as the predominant arsenic species in the livers of rats, and found cyclooxygenase-derived lipids as the inflammatory mediators before the development of overt liver injury for subchronic As4 S4 exposure. These mediators could translate into potential metabolic biomarkers in early arsenic risk assessment and as targets for therapeutic intervention.